LANGUAGE PORTFOLIO TECHNOLOGY AS A MEANS OF IMPROVING THE QUALITY OF LANGUAGE TRAINING IN A NON-LINGUISTIC UNIVERSITY (The Conference Hub, 2025)
In the modern world, personality formation takes place in new socio-economic and political conditions, which changes approaches to the organization of education and training. In recent years, there have been changes in the education system, which have led to the reevaluation of traditional teaching methods and the search for new technologies to optimize the educational process. The main task is to create conditions for the formation of personal autonomy of students, conducting adequate self-control and self-assessment in the process of learning a foreign language.